2012
DOI: 10.1093/cid/cis823
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Morbidity of Epstein-Barr Virus Infection in Pediatric Renal Transplant Recipients: A Multicenter, Prospective Study

Abstract: Presence of EBV high-risk seroconstellation, HLA-DR7, and intensity of immunosuppressive therapy are significant risk factors for a symptomatic EBV infection, whereas there is no close association between the degree or duration of EBV load and EBV-related morbidity. Clinical Trials Registration. NCT00963248.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 37 publications
9
81
3
Order By: Relevance
“…Since HLA-DR 13 is genetically linked to HLA-DQ6 (DQ β1 *06), especially in populations of European descent (35), it is possible that DQ β1 *06 might have contributed to EBV seronegativity as an HLA-DR β1*13-DQ β1 *06 haplotype in their cohort. In a study of 106 pediatric allograft recipients, Hocker and colleagues identified HLA-DR7 as an independent risk factor for EBV infection (36). Since HLA-DR7 is genetically associated with DQ β1 *02/*02, these results are consistent with our observation of a higher than expected proportion of HLA-DQ β1 *02 subjects that are seropositive.…”
Section: Discussionsupporting
confidence: 88%
“…Since HLA-DR 13 is genetically linked to HLA-DQ6 (DQ β1 *06), especially in populations of European descent (35), it is possible that DQ β1 *06 might have contributed to EBV seronegativity as an HLA-DR β1*13-DQ β1 *06 haplotype in their cohort. In a study of 106 pediatric allograft recipients, Hocker and colleagues identified HLA-DR7 as an independent risk factor for EBV infection (36). Since HLA-DR7 is genetically associated with DQ β1 *02/*02, these results are consistent with our observation of a higher than expected proportion of HLA-DQ β1 *02 subjects that are seropositive.…”
Section: Discussionsupporting
confidence: 88%
“…Though EB VL measurement in the whole blood was the most commonly used assay in this study (68 of 85 children), the actual peak VL was not helpful in predicting PTLD. A recent study by Hocker et al did not find correlation between EB VL and duration of VL with PTLD or EBV associated diseases [18]. Thus, this study and that by Hocker et al show that EB PVL alone has a low predictive value for PTLD.…”
Section: Discussioncontrasting
confidence: 46%
“…In our center, PTLD has been diagnosed in seven of the 252 RTx patients (3.7 %) and four of these had received their kidney graft as infants. Excellent articles on the management of CMV, EBV, and PV infections have recently been published [57][58][59][60][61].…”
Section: Infectionsmentioning
confidence: 99%